Scanning nonreciprocity spatial four-wave mixing process in moving photonic band gap. (25th January 2017) - Wang, Hang; Zhang, Yunzhe; Li, Mingyue; Ma, Danmeng; Guo, Ji; Zhang, Dan; Zhang, Yanpeng
Abstract: We experimentally investigate the scanning nonreciprocity of four-wave mixing process induced by optical parametric amplification in moving photonic band gap, which is different from the propagation nonreciprocity in the optical diode. Meanwhile the frequency offset and the intensity difference are observed when we scan the frequency of the beams on two arm ramps of one round trip. Such scanning nonreciprocities can be controlled by changing the frequency detuning of the dressing beams. For the first time, we find that the intensity difference can cause the nonreciprocity in spatial image. In the nonreciprocity process, the focusing or defocusing is resulted from the feedback dressing self-phase modulation while shift and split is attributed to feedback dressing cross-phase modulation. Our study could have a potential application in the controllable optical diode.